Impairment of the Plasmin Activation System in Primary Pulmonary Hypertension: Evidence for Gender Differences - Christ, Günter; Graf, Senta; Huber-Beckmann, Renate; Zorn, Gerlinde; Lang, Irene; Kneussl, Meinhard; Binder, Bernd R.; Huber, Kurt (Thrombosis and Haemostasis, 2001)
Primary pulmonary hypertension (PPH) is a rare disorder, with marked in-situ thrombosis of small pulmonary vessels occurring primarily in adult women. We investigated whether differences in the plasmin- and thrombin activation system are associated with the predominate affection of females. Plasma levels of plasminogen activator inhibitor type 1 (PAI-1), tissue-type plasminogen activator (t-PA), fibrinogen, thrombin-antithrombin (TAT) complexes, and prothrombin fragments (F1.2) were measured at baseline and after standardized venous occlusion (VO) in patients with PPH (24 female, 9 male). At baseline, females showed significant higher TAT levels (p = 0.05), higher t-PA antigen levels (p = 0.01) and higher fibrinogen levels (p = 0.03) with positive correlation to mean pulmonary artery pressure (mPAP), as well as nonsignificant lower t-PA activity, higher PAI-1 antigen and activity and F1.2 levels. After VO, females showed a significantly blunted increase in t-PA antigen (p = 0.01) and t-PA activity (p = 0.001), correlating with mPAP, as well as increased PAI-1 activity (p = 0.05). We hypothesize, that the observed presence of gender differences in the plasmin- and thrombin activation system in PPH leading to an antifibrinolytic/prothrombotic state might, in part, explain the female predominant incidence of this disease.
Keywords: Primary pulmonary hypertension; fibrinolysis; blood coagulation; gender